Vaccine nationalism: Competition, EU parochialism, and COVID-19. (30th March 2022) - Kampmark, Binoy; Kurečić, Petar
Abstract : This paper considers the forms of vaccine nationalism specific to responses to SARS-CoV-2. First, it considers the initial vaccine responses to SARS-CoV-2 and how the competition unfolded in a broader, global sense. The second part considers the way the European Union adopted its own type of nationalism, despite claiming to distinguish itself as more humanitarian and equitable in approaching COVID-19 vaccine production, supply, and distribution. The creation of the export control mechanism, and the threat of its use, was itself an expression of Euro-nationalism in action. The need to do so was largely a product of the EU's own making, given its own contractual relationships with the pharmaceutical companies. Finally, this paper contends that the advocacy for vaccine passports, championed by the EU, served to cause parochial ruptures in the bloc for commercial reasons.